Participatory Forest Carbon Assessment and REDD+: Learning from Tanzania - Kusaga Mukama; Irmeli Mustalahti; Eliakimu Zahabu (International Journal of Forestry Research)
Research initiatives and practical experiences have demonstrated that forest-related data collected by local communities can play an essential role in the development of national REDD+ programs and its' measurement, reporting, verification (MRV) systems. In Tanzania, the national REDD+ Strategy aims to reward local communities participating in forest management under Participatory Forest Management (PFM). Accessing carbon finances requires among other things, accurate measurements of carbon stock changes through conventional forest inventories, something which is rarely done in PFM forests due to its high cost and limited resources. The main objective of this paper is to discuss experiences of Participatory Forest Carbon Assessment (PFCA) in Tanzania. The study revealed that villagers who participated in PFCA were able to perform most steps for carbon assessment in the field. A key challenge in future is how to finance PFCA and ensure the technical capacity at local level.